Lamellar MWW-Type Zeolites: Toward Elegant Nanoporous Materials - Anderson Schwanke; Sibele Pergher (Applied Sciences, 2018)
This article provides an overview of nanoporous materials with MWW (Mobil twenty two) topology. It covers aspects of the synthesis of the MWW precursor and the tridimensional zeolite MCM-22 (Mobil Composition of Matter number 22) as well as their physicochemical properties, such as the Si/Al molar ratio, acidity, and morphology. In addition, it discusses the use of directing agents (SDAs) to obtain the different MWW-type materials reported so far. The traditional post-synthesis modifications to obtain MWW-type materials with hierarchical architectures, such as expanded, swelling, pillaring, and delaminating structures, are shown together with recent routes to obtain materials with more open structures. New routes for the direct synthesis of MWW-type materials with hierarchical pore architecture are also covered.